Accuracy of digital bitewing radiographs with and without applying horizontal tube shift in the diagnosis of residual excess cement around dental implants: An in vitro study - Zahra Dalili Kajan; Hamid Neshandar Asli; Negar Khosravifard; Maryam Bidvand; Elahe Rafiei (Universidad de Concepción., 2021)
Purpose: This study was designed to evaluate the diagnostic value of digital Bitewing (BW) radiographs with and without horizontal tube shift in detecting Residual excess cement (REC) on the proximal and non-proximal surfaces of implant restorations. Material and Methods: Eight mandibular models were fabricated with two implants placed on each side in the premolar and first molar positions. Excess cement was applied to either proximal or non-proximal surfaces of the restorations intentionally during the process of crown cementation. BW radiographs with and without applying horizontal tube shift were acquired. Three maxillofacial radiologists were asked to determine the presence and location of REC in the radiographs. Sensitivity and specificity of the radiographic technique were assessed according to the restoration surface that contained REC. Results: Sensitivity of BW radiographs was 100% for the detection of REC on the proximal surfaces and 41-18, 80% on the non-proximal surfaces. Specificity of the technique was 85.71%-100% for the proximal surfaces and 75-94. 12% for the non-proximal areas. Specificity of the radiographic method was generally greater than its sensitivity for the non-proximal surfaces while in the proximal areas, the two variables had quite similar values. Conclusion: Digital BW radiography is generally more useful for detection of REC on the proximal surfaces. Higher specificity of this technique for the bucco-lingual surfaces suggests more reliability of the negative diagnoses in the non-proximal areas.